Prediction of Fuzzy Sunspot Time Series By Using RBFANN - Azher. A. Mohamad; Nazar.K.Hussein; Ibrahim. A. Morbat (Tikrit Journal of Pure Science, 2023)
We are present in this paper a new modified method of prediction of  Sunspot time series after Fuzzify the data by using Fuzzy C-means clustering method (FCM). Our method consist of forecasting as first phase and prediction as a second phase. The accuracy of the results that we obtained is measured by M.S.E and we got a good results.